Improving compliance to osteoporosis workup and treatment in postmenopausal patients after a distal radius fracture - Roy Kessous; Adi Y. Weintraub; Yoav Mattan; Rivka Dresner-Pollak; Mayer Brezis; Meir Liebergall; Leonid Kandel (Elsevier, 2014)
Objective: Distal radius fracture (DRF) in postmenopausal women is often the first clinical sign of osteoporosis (OP). Despite the availability of effective treatments, only a minority of patients who sustain a fragility fracture are tested for OP. The purpose of this study was to examine whether a simple intervention by the hospital staff increases rates of OP workup. Materials and Methods: We conducted a prospective randomized clinical trial. Ninety nine patients after DRF were randomized to two groups. Both groups were contacted after their fracture and were asked to answer a questionnaire and were informed about the possible relationship between DRF and OP. In the intervention group, patients were sent an explanatory pamphlet and a letter to their primary care physician. An additional survey was conducted to establish whether the intervention improved the number of patients who undergo OP workup. Results: The intervention increased the proportion of patients who turned to their primary care physician from 22.9% to 68.6%, and increased the proportion of patients undergoing OP workup from 14.3% to 40% (p < 0.001). Conclusion: Women with DRF who receive an explanation about possible OP implications and are sent explanatory materials are more likely to undergo OP workup.